If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(x + 2) + 6(x + 2) = 5x + -5 Reorder the terms: 7(2 + x) + 6(x + 2) = 5x + -5 (2 * 7 + x * 7) + 6(x + 2) = 5x + -5 (14 + 7x) + 6(x + 2) = 5x + -5 Reorder the terms: 14 + 7x + 6(2 + x) = 5x + -5 14 + 7x + (2 * 6 + x * 6) = 5x + -5 14 + 7x + (12 + 6x) = 5x + -5 Reorder the terms: 14 + 12 + 7x + 6x = 5x + -5 Combine like terms: 14 + 12 = 26 26 + 7x + 6x = 5x + -5 Combine like terms: 7x + 6x = 13x 26 + 13x = 5x + -5 Reorder the terms: 26 + 13x = -5 + 5x Solving 26 + 13x = -5 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. 26 + 13x + -5x = -5 + 5x + -5x Combine like terms: 13x + -5x = 8x 26 + 8x = -5 + 5x + -5x Combine like terms: 5x + -5x = 0 26 + 8x = -5 + 0 26 + 8x = -5 Add '-26' to each side of the equation. 26 + -26 + 8x = -5 + -26 Combine like terms: 26 + -26 = 0 0 + 8x = -5 + -26 8x = -5 + -26 Combine like terms: -5 + -26 = -31 8x = -31 Divide each side by '8'. x = -3.875 Simplifying x = -3.875
| 2(4x+1)+4(x-3)= | | 10x+9-(4)=9x-(4) | | 600+0.9x=1.5x | | a+6=-7 | | 11x+5=4x+47 | | 51+7x=96 | | 2a+6a+3a-7= | | 2x+38-5x=3-6x+5 | | -7x+9=30(-3) | | -6=6(x-6)+3x | | -8y^2+2y^2+6=0 | | 51+7x=72 | | 9.6z-4.2=14.7+6.9z | | -5y+3=-5y+6 | | 12w^2+8w=-7w^2-3w+14 | | 3(8-x)=6 | | x+5=43 | | 12-6z=9z+2 | | (8p-1)(64p^2+8p+1)= | | 3c-24=6(c-4) | | -3(2/3)=-2 | | 7+18x-1=9x+134-7x | | 11.3p-1=5(p-1)-2(7-2p) | | 5(9c-1)-2=43c+5 | | x^3-2x+4= | | (2x-3)(2x-3)(2x-3)=7 | | 5(4c-1)-1=18c+4 | | 5-2(3x+2)=17 | | 5(x-7)-3x=4(x-3)-1 | | 9(x-4)=2 | | 5x+3=-16(-3) | | -14x-20=-11x+55 |